Theoretical model estimation of guest diffusion in metal–organic frameworks (MOFs). Issue 86 (18th September 2015) - Zheng, B.; Huang, K.-W.; Du, H.
<x xml:space="preserve">Abstract</x> An analytical model was developed to efficiently and accurately estimate the guest diffusivity in flexible metal–organic frameworks (MOFs).